Impact of a clinical program using weekly Short Message Service (SMS) on antiretroviral therapy adherence support in South Africa: a retrospective cohort study. Issue 1 (December 2017) - Georgette, Nathan; Siedner, Mark; Petty, Carter; Zanoni, Brian; Carpenter, Stephen; Haberer, Jessica
Abstract Background In randomized controlled trials, short message service (SMS) programs have improved adherence to HIV antiretroviral therapy (ART). In response, the World Health Organization recommended use of SMS programs to support ART. However, there is limited data on real-world implementations of SMS programs. Methods We conducted a retrospective cohort study of an SMS program to improve ART adherence in a government-run HIV clinic in rural South Africa. We analyzed data from all adult patients who 1) enrolled at the clinic before the observation period (July 2013 through June 2014), 2) had ≥1 ART prescriptions in the observation period, and 3) had data on phone number availability (N = 2255). Our main outcome measure was prescription coverage, defined as the presence of a valid ART prescription for each day observed. We fit generalized linear mixed models adjusted for pre-program prescription coverage, demographics, and ART duration, dosing, and regimen. Results Exposure to the SMS program was independently associated with greater prescription coverage (AOR = 1.23, 95% CI 1.13–1.34, P < 0.001) compared with non-exposure, although the absolute increase in prescription coverage was small (4.7 days of ART prescription coverage per average patient per year). Among a subset of patients (n = 725) whose pre-program prescription coverage was <100%, the corresponding mean expected absolute increase in prescription coverage was 8.2 days per year. Conclusions Our primary finding was that an SMS reminder program implemented in routine clinical care was associated with a small increase in prescription coverage of uncertain clinical significance.